Religious-digital tensions among Muslim Gen Z tourists: Phenomenology of NTB halal tourism - Kurnia, Agus; Sugiyanto, Catur; Purnomo, Boyke Rudy; Kusworo, Hendrie Adji (Faculty of Business & Economics, Universitas Islam Indonesia, 2026)
Purpose – This study investigates the religious–digital tensions experienced by Muslim Gen Z tourists in West Nusa Tenggara (NTB), Indonesia, arising from the gap between their expectations of an integrated digital–halal ecosystem and the realities of infrastructure and destination governance. It conceptualizes these tensions as a systemic phenomenon with implications for the Islamic management of halal tourism.Methodology – A qualitative phenomenological approach was employed using interpretative phenomenological analysis (IPA), combining in-depth interviews with seven participants and a focus group discussion (FGD) with four, totalling eleven Muslim Gen Z tourists selected purposively. Data were analyzed inductively and deductively, supported by member checking, back-translation, and source triangulation. Findings – The analysis reveals six interrelated tension clusters: (1) universal connectivity versus discriminatory signals, (2) cashless ecosystem versus partial payment infrastructure, (3) digital halal certification versus informal trust, (4) comfortable halal accommodation versus rigid formalization, (5) accessible Islamic finance versus limited outreach, and (6) responsive versus fragmented governance. These tensions form a layered compound system across infrastructural, informational, and conceptual–regulatory levels.Implications – The findings offer strategic recommendations for destination managers, Islamic financial institutions, and halal certification bodies to close the implementation gap in NTB's halal tourism, transferable within specified scope conditions to comparable subnational halal-branded destinations worldwide.Originality – This study is among the first to conceptualize halal tourism tensions as a layered compound system through IPA of Muslim Gen Z tourists in a Muslim-majority subnational destination in India. It formally defines digitally compounded halal risk as an extension of Perceived Halal Risk.